PENGARUH LINGKUNGAN KERJA,KARAKTERISTIK PEKERJAANDAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Agustinus I Gede Muliarsa; Gde Bayu Surya Parwita; Ni Nyoman Suryani; Ni Wayan Ari Sudiartini,SE.,M.Si (Universitas Mahendradatta, 2021)
For the progress of its business, the company seeks to improve the performance of its employees in order to satisfy consumers by prioritizing good and friendly service quality. This study aims to determine the influence between work environment and job characteristics. and work discipline on employee performance. The population in this study were all employees of PT. Raditya Dewata Perkasa, amounting to 175 people. The sample in this study was 64 people. The determination of the sample in this study was using the Slovin method. The data collection methods used in this study were by conducting observations, interviews, and by distributing questionnaires. The analysis used in this research is multiple linear regression analysis techniques. The analytical tool used is SPSS 23.0. The results of this study indicate: 1) work environment variables have a positive and significant effect on employee performance. 2) Job characteristics variables also have a positive and significant effect on employee performance. 3) Work discipline variables also have a positive and significant effect on employee performance